2021
DOI: 10.5114/fmpcr.2021.108185
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the factors causing malnutrition and its impact on mortality among under-five Bangladeshi children

Abstract: Background. Nutritional status is the best indicator of global well-being. Childhood malnutrition is a major public health problem among Bangladeshi children. Objectives.The main objectives of this study are to: (i) determine the prevalence of malnutrition among under-five (U5) children; (ii) assess the association between malnutrition and selected factors; (iii) determine the high-risk factors for malnutrition and its impact on U5 mortality. Material and methods. The data was taken from the Bangladesh Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
3
2
1
Order By: Relevance
“…In Bangladesh, the rate of stunted children is considered to be higher than the rate of underweight and wasted problems due to the high incidence of childhood infections, and maternal anxiety during pregnancy. A similar finding is revealed in previous research (Ahmed et al, 2021;Dewey & Begum, 2011;WHO, 2021) and a previous study showed the reverse findings (Querol et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In Bangladesh, the rate of stunted children is considered to be higher than the rate of underweight and wasted problems due to the high incidence of childhood infections, and maternal anxiety during pregnancy. A similar finding is revealed in previous research (Ahmed et al, 2021;Dewey & Begum, 2011;WHO, 2021) and a previous study showed the reverse findings (Querol et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…One of the logical reasons behind this may be the lack of adequate time for the child due to the busy schedule of working mothers. Similar findings are exhibited in the several preceding studies (Ahmed et al, 2021 ; Chowdhury et al, 2016 ). It is a common belief that if a child suffers from different childhood morbidity, the child has the possibility to become a malnourished child.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with several studies conducted in India, Ethiopia, and twenty-three sub-Saharan African countries [13][14][15], which showed that socioeconomic status (age, residence of children), maternal education and household income were associated with vitamin A intake. However, our study found no significant association between maternal education and VAS, as was also the case in Bangladesh when Manoj Kumar Raut [16] conducted a secondary analysis on 4852 children with DHS 2007 data and found no association, although a significant association was obtained on 7,087 children with DHS 2011 data; more generally, higher maternal education is positively associated with better child health and survival [17][18][19].…”
Section: Discussioncontrasting
confidence: 45%
“…The term 'malnutrition' is used to encompass both undernutrition and overnutrition in humans (Ahmed et al, 2021;Garanet, 2020;Sumon, Hossain, Ar Salan, et al, 2023), which are barriers to good health characterised by an inadequate intake of calories and nutrients, which can cause disease and, in severe cases, death (Sumon, Hossain, Ar Salan, et al, 2023). The scarcity of affordable, nutrient-dense food options influences children's health (Hossain, Huq, & Abdulla, 2023).…”
Section: Introductionmentioning
confidence: 99%